Pengaruh ekstrak jintan hitam (Nigella sativa) terhadap kadar SGPT hepar tikus (Rattus norvegicus) yang diinduksi Piroxicam - Septiana Kurniasari; Moch. Haikal (Universitas Sultan Ageng Tirtayasa, 2021)
Piroxicam is a non-steroidal anti-inflammatory drug (NSAID) that can cause side effects on the liver. If the liver is affected by side effects from using Piroxicam, it can cause cell damage so that the hepatic organs' function and work are disturbed. The biomarker of liver damage is the SGPT level. An increase in the SGPT ratio indicates serious liver damage. One way to minimize liver damage is by giving antioxidants. One of the many herbal plants used to prevent or treat various diseases is black cumin (Nigella sativa). This study aimed to analyze the effect of black cumin extract on the liver SGPT levels of Piroxicam-induced rats. Eighty male mice were used in this study and were divided into three groups, namely the negative control group (K-), Piroxicam non-extract (P-), and Piroxicam plus extract (P +). Black cumin extract is given orally at a dose of 2 gr / kgBW; 3 gr / kgBB; 4 gr / kgBB; 5 gr / kg body weight and 6 g / kg body weight, while the Piroxicam dosage given is 1 g / kg and 3 g / kg body weight. The results showed that the more Piroxicam doses were given, the higher the SGPT level. Along with the increase in the dose of black cumin extract, the SGPT level is reduced.